Anisotropic softening model for masonry plates and shells - Lourenço, Paulo B. (2000)
A model for the numerical analysis of masonry subjected to out-of-plane loading is proposed. The proposed composite plasticity model is able to reproduce elastic and inelastic behavior in two orthogonal directions coinciding with the orientation of the bed and bead joints of masonry. The implementation of the model is described, and a comparison with experimental data on masonry strength is provided. Good agreement is found for different masonry types. Further validation of the model with experimental results on masonry panels subjected to out-of-plane loading demonstrates the accuracy of the proposed approach and the possibilities offered by numerical analysis for the understanding of the complex nonlinear phenomena involved in the failure of masonry plates and shells. In particular, this paper addresses issues such as the adequacy of yield-line analysis for the design of masonry structures subjected to out-of-plane loading, the influence of the aspect ratio of the panels, and the influence of in-plane normal pressure.